A hydrocolloid based biorefinery approach to the valorisation of mango peel waste. (April 2018) - Banerjee, Jhumur; Singh, Ramkrishna; Vijayaraghavan, R.; MacFarlane, Douglas; Patti, Antonio F.; Arora, Amit
Abstract: An environment-friendly hydrothermal process was developed to extract pectin from a horticultural waste, namely mango peels, at a reasonable temperature and pressure. High average yields of pectin (15.7%, 27.2%) were obtained from the two mango cultivars namely, Calypso (Australian) and Totapuri (Indian). The physico-chemical characteristics were determined in terms of the degree of esterification (77–89%), molecular weights (Mw ) (49, 742–49, 862 Da), FTIR and gelling tests. The spent liquor was hydrolysed to recover the specific polyphenols and sugars. The polyphenols in the hydrolysed liquid were quantified as gallic acid (525.1–1405.6 mg/l), mangiferin (7.8–162.2 mg/l), quercetin (40.6–49.2 mg/l) and ellagic acid (38.8–69.3 mg/l). The solid residue obtained as a solid co-product after pectin extraction was found to be rich in cellulose (38%) and lignin (16%). In this paper, an attempt has been made to address the challenges of the extraction of pectin from mango peels, in a conventional process. It was demonstrated that mango peels may be a promising unconventional source for recovery of food-grade quality pectin. Considerable efforts, which were earlier expended in the processing, were reduced when recovery of other food-grade co-products was integrated with the process of hydrocolloid extraction. Graphical abstract: Image 1 Highlights: Mango peels were valorized in an environmental friendly process to recover pectins with high degree of esterification. The obtained pectin extracts in hydrothermal process were qualitatively similar to commercial citrus pectin. The liquid pectin co-product was found to be a rich source of polyphenols such as gallic acid, mangiferin and quercetin. Multiple products recovery option via proposed pathway is an attractive proposition compared to conventional process.